Electrification and Women's Empowerment : Evidence from Rural India - Samad, Hussain (World Bank, Washington, DC, 2019)
Electrification has been shown to accelerate opportunities for women by moving them into more productive activities, but whether improvements in economic outcomes also change gender norms and practices within the household remains unclear. This paper investigates the causal link between electricity access and women's empowerment, using a large gender-disaggregated data set on India. Empowerment is measured by women's decision-making ability, mobility, financial autonomy, reproductive freedom, and social participation. Using propensity score matching, the study finds that electrification enhances all measures of women's empowerment and is associated with an 11-percentage point increase in the overall empowerment index. Employment and education are identified as the two most important causal channels through which electrification enables empowerment.